Pengaruh Profitabilitas, Ukuran Perusahaan, Opini Auditor, Dan Umur Perusahaan Terhadap Audit Delay Pada Perusahaan Sektor Perdagangan Eceran - Juanta, Darwen; Ratih, Suklimah (Jurnal Syntax Fusion, 2021)
Audit Delay is the duration needed for completion of the financial statement audit performed by the auditor measured from the date of the company's annual financial statements, to the date of the issuance of the independent audit report. The longer an Audit Delay will have a negative impact and will delay the publication of financial statement information which can affect economic decision making. The purpose of this study is to examine and determine the effect of Profitability, Company Size, Auditor Opinion, and Company Age on Audit Delay in retail trade sector companies in 2017-2019. This study uses data from retail trade sector companies in 2017-2019. After selecting the sample, there were 21 companies selected in this study. The statistical test used in this research is a descriptive statistical test. While the hypothesis test used multiple linear regression tests. The results of this test indicate that (1) Profitability and Auditor Opinion have negative effect on Audit Delay. (2) based on the conducted research, it can be seen that company size and company age have no effect on audit delay.